Antithrombotic, Antihemolytic Activities and Protein Conjugation Properties of Silver Nanoparticles Synthesized from Turbinaria ornata - Venkatesan, Amalan; Vinoth Raja Antony Samy, Jose; Ranga Anantha Sayanam, Rajeswari; Rajendran, Jayaprakash; Natesan, Vijayakumar (Asian Journal of Chemistry, 2021)
Green synthesis of silver nanoparticles synthesized from Turbinaria ornata weed extract was carried out. Because these seaweeds are largely unexplored and contain botanical molecules that promote bimolecular reduction. In this study, silver nanoparticles (AgNPs) cause a rise in the accumulation of clotting factors, platelets and procoagulant activity, both of which lead to thrombotic and hemolytic diseases. The silver nanoparticles were initially characterized using spectroscopic analysis to validate the biomolecules of Turbinaria ornata involved in nanoparticle reduction. A detailed study on the effectiveness of silver nanoparticles on antithrombolytic activity in adult blood samples confirms the interaction of nanoparticles with platelets and blood vessels, which is significant in the production of thrombosis and cardiovascular diseases. The antihemolytic activity was tested to assess the percentage of blood clot lysis in order to confirm the ability to scavenge hydrogen peroxide in a concentration dependent manner. The protein conjugation and binding activities of major, secondary, and tertiary structures were also investigated in silico. Thus, Turbinaria ornata seaweeds with reduced silver nanoparticles demonstrated increased antithrombotic and antihemolytic activities, suggested that they could be used as novel therapeutics for cardiovascular diseases.